Anaesthesia and resuscitation a manual for medical students. - Gordon, Roderick Angus, 1911- (Book collections on Project MUSE., 1973)
As in most fields of medical practice many things in anaesthesia are done on an empirical basis: this speciality is dynamic and expanding, and today's dogma may become tomorrow's error. This introductory manual, now revised and updated in a second edition, was prepared by the Department of Anaesthesia in Canadian medical schools and provides the undergraduate medical student with an important foundation for wider knowledge in the realm of anaesthesiology. Contents include Anaesthesia in relation to surgery, Evaluation of the patient before anaesthesia, Preanaesthetic medication, General anaesthesia, Neuromuscular transmission and muscle relaxation, Regional anaesthesia, Care of the unconscious patient, Respiration and anaesthesia, Cardiovascular homeostasis in relation to anaesthesia and resuscitation, Fluid and electrolyte balance, Acid-base balance, Complications of anaesthesia, Postoperative problems and care, Obstetrical anaesthesia and resuscitation of the newborn, and Special considerations in paediatric anaesthesia.